The determination of 22 natural brassinosteroids in a minute sample of plant tissue by UHPLC-ESI-MS/MS - Tarkowská, Danuše; Novák, Ondřej; Oklestkova, Jana; Strnad, Miroslav (Analytical and bioanalytical chemistry, 2016)
The triterpenoid plant hormones brassinosteroids (BRs) are believed to influence almost every aspect of plant growth and development. We have developed a sensitive mass spectrometry-based method for the simultaneous profiling of twenty-two naturally occurring brassinosteroids including biosynthetic precursors and the majority of biologically active metabolites. Using ultra-high performance liquid chromatographic (UHPLC) analysis, the run time was reduced up to three times (to 9 min) in comparison to standard HPLC BRs analyses, the retention time stability was improved to 0.1-0.2 % RSD and the injection accuracy was increased to 1.1-4.9 % RSD. The procedures for extraction and for two-step purification based on solid-phase extraction (SPE) were optimised in combination with subsequent UHPLC analysis coupled to electrospray ionisation tandem mass spectrometry (ESI-MS/MS) using Brassica flowers and Arabidopsis plant tissue extracts. In multiple reaction monitoring (MRM) mode, the average detection limit for BRs analysed was close to 7 pg, and the linear range covered up to 3 orders of magnitude. The low detection limits for this broad range of BR metabolites enabled as little as 50 mg of plant tissue to be used for quantitative analyses. The results of determinations exploiting internal standards showed that this approach provides a high level of practicality, reproducibility and recovery. The method we have established will enable researchers to gain a better understanding of the dynamics of the biosynthesis and metabolism of brassinosteroids and their modes of action in plant growth and development.
Keywords: extrakce na pevné fázi; rostlinné extrakty; Plant Extracts; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Limit of Detection; Solid Phase Extraction; Arabidopsis; hmotnostní spektrometrie s elektrosprejovou ionizací; reprodukovatelnost výsledků; limita detekce; Brassica napus; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Spectrometry, Mass, Electrospray Ionization; brassinosteroidy; Tandem Mass Spectrometry; Brassinosteroids